THE RELATION OF POWER IN FILM ‘THE JUDGE’: A CRITICAL DISCOURSE ANALYSIS - Wahyuni, Sri; Setyowati, Yulis; Probowati, Yeni (Universitas PGRI Sumatera Barat, 2024)
This research explores how discourse, actors, societal structures, power dynamics, and illocutionary acts play significant roles in shaping communication and influencing individuals' beliefs and attitudes. It emphasizes the importance of analyzing language and social interactions to gain a deeper understanding of how power and meaning are constructed and perpetuated in society. The researcher employed the concept of code-switching to interpret the film